PENGATURAN SUHU DESTILATOR PADA PROSES DESTILASI BIO-ETANOL BERBASIS KENDALI PROPORSIONAL MENGGUNAKAN PLC OMRON CPM2A - Paulus Tofan Rapiyanta; Bambang Sutopo; Indah Soesanti (Paradigma, 2012)
Temperature control is the most important thing in destilation process. This research has a purpose to create appliance assist that able to do temperature’s monitoring and controlling function during destilation process. In this research, temperature’s control was applied in bioetanol’s destilation which uses Omron’s PLC type CPM2a. Proportional control design used Ziegler-Nichols method. Proportional control is made based on delphi programming algorithm.Controlling program in delphi connected with destilation plant through PLC. PLC get temperature data from LM35 censor then delivered to controller program in delphi. Controller’s data output will be sent through PLC to control heater power. Change of heater power will influence temperature of destilation plant. Stability of destilator temperature will be used to analysing system performance. The result of this research is the stable destilator temperature controller system between 78 until 80ºC. At the moment, oscilation still happened with steady state error below 3%. 1 litre of raw material can be destilated during one hour and can get about 100 ml etanol with rate 70%.Keywords : Proportional controller, distillation, etanol